2014
DOI: 10.1080/00288233.2013.855244
|View full text |Cite
|
Sign up to set email alerts
|

Field studies assessing the effect of dicyandiamide (DCD) on N transformations, pasture yields, N2O emissions and N-leaching in the Manawatu region

Abstract: Nitrification inhibitors (NI) allow retention of soil nitrogen (N) in the ammonium (NH 4 + ) form for longer periods. Therefore, they can potentially increase pasture yields by decreasing N losses via nitrous oxide (N 2 O) emissions and nitrate (NO 3 − ) leaching. Multiple field experiments were conducted over 3 years at a Massey University dairy farm in the Manawatu region to determine the effect of the NI dicyandiamide (DCD) on soil N transformations, N 2 O emissions, pasture yields and NO 3 − leaching. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
4
4
0
Order By: Relevance
“…2; Table 2). Similar findings on the effectiveness of broadcasting DCD at 10 kg ha −1 for reducing N 2 O emissions have been reported in other studies (e.g., de Klein et al 2011;Luo et al 2013;Cameron et al 2014;de Klein et al 2014;Kim et al 2014;Ledgard et al 2014). Ledgard et al (2008) developed a novel-patented approach to strategic application of DCD to urine patches by directly administering the DCD to animals.…”
Section: Urine Application and N 2 O Emissionssupporting
confidence: 89%
See 2 more Smart Citations
“…2; Table 2). Similar findings on the effectiveness of broadcasting DCD at 10 kg ha −1 for reducing N 2 O emissions have been reported in other studies (e.g., de Klein et al 2011;Luo et al 2013;Cameron et al 2014;de Klein et al 2014;Kim et al 2014;Ledgard et al 2014). Ledgard et al (2008) developed a novel-patented approach to strategic application of DCD to urine patches by directly administering the DCD to animals.…”
Section: Urine Application and N 2 O Emissionssupporting
confidence: 89%
“…As discussed earlier, DCD is subject to degradation and leaching from the surface soil where urine has accumulated and N 2 O is being produced, leading to lower efficiency of DCD use (Luo et al 2008;Shepherd et al 2012;Kelliher et al 2014). Compared with the southern part of country, DCD would be less effective in the northern North Island of New Zealand, where the present study was conducted, due to warmer soil temperatures in winter de Klein et al 2014;Kim et al 2014;Ledgard et al 2014), as an increase in soil temperature has been shown to decrease the efficacy of DCD (Puttanna et al 1999). As well, the current study was conducted on a free-draining volcanic soil, which has naturally high rates of nitrification (Sarathchandra 1978) and rainfall/ drainage levels that are generally higher than those in many other dairying regions.…”
Section: Dcd Application Ratementioning
confidence: 89%
See 1 more Smart Citation
“…The results of trials in Waikato, Manawatu and Canterbury are presented in associated papers (Ledgard et al 2014;Kim et al 2014 andCameron et al 2014, respectively). This paper reports the results from the NOMR trial in South Otago.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of ammonium nitrogen in the soil increased under nitrification inhibitor application. In another study, it was determined that, the application of dicyandiamide reduced NO3 -leaching by 22% (Kim et al, 2014). A series of studies reported by Di and Cameron over the past few years show a reduction of about 60 relative % in NO3 -leaching (Di and Cameron, 2005;Di and Cameron, 2006;Di et al, 2007;Singh and Verma, 2007).…”
Section: Discussionmentioning
confidence: 96%